2020
DOI: 10.35772/ghm.2020.01013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of volume on outcome in hepatobiliary surgery: a review with guidelines proposal

Abstract: The positive relationship between volume and outcome in hepatobiliary surgery has been demonstrated for many years. As for other complex surgical procedures, both improved short-and long-term outcomes have been associated with a higher volume of procedures. However, whether the centralization of complex hepatobiliary procedures makes full sense because it should be associated with higher quality of care, as reported in the literature, precise criteria on what to centralize, where to centralize, and who should … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 55 publications
1
6
0
2
Order By: Relevance
“…In line with previous studies, treatment at a high-volume hospital or by a high volume surgeon was signi cantly associated with good medical outcomes [15][16][17]. A previous study of a nationwide population provided additional insight into the combined effects of surgeon volume and hospital volume on survival after hepatic resection.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In line with previous studies, treatment at a high-volume hospital or by a high volume surgeon was signi cantly associated with good medical outcomes [15][16][17]. A previous study of a nationwide population provided additional insight into the combined effects of surgeon volume and hospital volume on survival after hepatic resection.…”
Section: Discussionsupporting
confidence: 78%
“…Another study reviewed proposed guidelines for hepatobiliary surgery and addressed the effects of volume on outcomes of hepatobiliary surgery. The authors recommended the establishment of an expert panel to draft preparatory and preliminary agreements on the clari cation and standardization of technical terminology used to discuss HCC resection and indicators for HCC resection [16]. Lu et al retrospectively analyzed 23,107 major hepatectomies for HCC patients and concluded that surgeon volume and hospital volume are signi cant independent predictors of postoperative recurrence (p<0.001) [17].…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that high-volume surgeons have better outcomes than colleagues working in low-volume centers for colorectal [ 88 ], esophageal [ 89 ], and hepatobiliary [ 90 ] minimally invasive interventions. Also for emergency general surgery, data suggest an association between low-volume surgery and a higher risk of postoperative adverse events [ 91 ], particularly in frail populations [ 92 , 93 ].…”
Section: Resultsmentioning
confidence: 99%
“…We are aware that center volume correlates to results ( 55 58 ), but in a moment in which health migration constitutes a risk for the population due to the COVID19 pandemic ( 59 , 60 ), a Hub and Spoke Program for elective BS may offer patients the chance to be treated in the safest and most effective way without the costs and risks of health migration ( 20 ).…”
Section: Discussionmentioning
confidence: 99%